AI dalam Pembelajaran Bahasa: Evaluasi Keefektivan Alat Pengenalan Ucapan dalam Kelas Bahasa Arab Mahasiswa Pendidikan Bahasa Arab IAIN Pontianak tahun 2020 - Halisah, Atikah Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Technological advancements, particularly in artificial intelligence (AI), have brought significant changes to the field of education, including foreign language learning. AI-based speech recognition technology offers a new approach that can enhance students' speaking skills by providing real-time feedback. This study aims to evaluate the effectiveness of AI speech recognition tools in foreign language classrooms, analyzing ease of access, accuracy in detecting pronunciation errors, and technical challenges faced by students. The results indicate that most students find AI to be quite effective in helping them understand pronunciation and detect errors. However, challenges such as technical difficulties and limitations in detecting more complex language nuances still need to be addressed. Nevertheless, the overall use of AI in foreign language learning has been well received by students, showing great potential for further development in supporting more personalized and efficient learning. This research employs a quantitative survey method to collect data from students using AI-based speech recognition tools in learning Arabic. The researcher uses a questionnaire as the primary instrument. AI-based speech recognition tools have proven effective in improving students' speaking skills in foreign language classrooms. This study suggests that integrating AI technology into language learning can provide significant benefits, such as improved pronunciation and increased student motivation. However, further research is needed to explore potential challenges and optimize the use of these tools in various learning contexts